2019
DOI: 10.3390/molecules24142581
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Carotenoids and Fat-Soluble Vitamins from Tetradesmus Obliquus Microalgae: An Optimized Approach by Using Supercritical CO2

Abstract: In recent years, great attention has been focused on rapid, selective, and environmentally friendly extraction methods to recover pigments and antioxidants from microalgae. Among these, supercritical fluid extraction (SFE) represents one of the most important alternatives to traditional extraction methods carried out with the use of organic solvents. In this study, the influence of parameters such as pressure, temperature, and the addition of a polar co-solvent in the SFE yields of carotenoids and fat-soluble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…As hydrophobic, membrane-embedded compounds, menaquinones are not produced extracellularly and continuously, but remain cell-associated in all producing bacteria. Nevertheless, simple and efficient procedures are being continuously developed and optimized for extracting vitamin K2 and other valuable cell-associated molecules from biomass [3739], that, together with the knowledge obtained from this study, will facilitate the biotechnological production of long-chain vitamin K2.…”
Section: Discussionmentioning
confidence: 99%
“…As hydrophobic, membrane-embedded compounds, menaquinones are not produced extracellularly and continuously, but remain cell-associated in all producing bacteria. Nevertheless, simple and efficient procedures are being continuously developed and optimized for extracting vitamin K2 and other valuable cell-associated molecules from biomass [3739], that, together with the knowledge obtained from this study, will facilitate the biotechnological production of long-chain vitamin K2.…”
Section: Discussionmentioning
confidence: 99%
“…All of these, suggest microalgae enriched food as a good source of nutritional supplements especially for strict vegetarians owing to its rich high-value nutrients as well as Vitamin B 12 . Chronopoulou et al [ 102 ] proposed an improved approach to extract fat-soluble vitamins by using supercritical CO 2 while a previous study compared six extraction methods for Vitamin B 12 from Spirulina and found the aqueous extraction suits best for this studied compound [ 103 ].…”
Section: Microalgae In Nutraceuticals/foodmentioning
confidence: 99%
“…are another reservoir of provitamin A (Kay and Barton, 1991). Chronopoulou et al, has reported that extraction of vit A from Tetradesmus Obliquus is in the highest amount through supercritical fluid extraction method (Chronopoulou et al, 2019). Higher intake of dietary Vit A can remarkably decrease the ovarian, lung, gastric, pancreatic, and cervical carcinoma risk (Sanusi, 2019;Wang and He, 2020).…”
Section: Vitaminsmentioning
confidence: 99%